The Effect of Feeding Elevated Levels of Tilapia (Oreochromus niloticus) By-product Meal on Broiler Performance and Carcass Characteristics - Maigualema, M.A.; Gernat, A.G. (International Journal of Poultry Science, 2003)
broilerThe tilapia industry has grown significantly. Considerable processing waste is generated by the tilapia industry because only the myomere (fillets) muscles are removed and marketed. This portion constitutes approximately 36% of the entire fish, leaving the remaining 64% of the fish as waste lost during the various processing operations. This waste recovered from the tilapia processing plant has the potential of being an alternative protein source in broiler rations. The objective of this study was to measure the effect of substituting elevated levels of tilapia by-product meal (TBM) for soybean meal (SBM) in broiler diets. Crude protein from TBM was substituted for SBM crude protein at a rate of 0, 25, 50, 75, and 100%. The control and four concentrations of TBM were used in a typical corn-soybean based diet and fed to chicks from 0-42 days of age. Chicks were randomly allocated to a ration using a randomized complete block design. Body weight, cumulative feed consumption, feed conversion ratio, and mortality was determined on a weekly basis. Processing carcass weights and yields were determined on a pre-chilled basis. The results showed that chicks fed 0, 25 and 50% TBM had significantly (P < 0.01) higher body weights, feed consumption and improved feed conversion throughout the 42 d growing period as compared to the other treatments. Carcass weights were also significantly (P < 0.01) higher. No significant differences were found for mortalities or yields for any of the treatments. In conclusion, the results show that TBM can be substituted for SBM crude protein up to a 50% level without negatively affecting bird performance or carcass quality.